Investment Analytics, Fintech, Risk Perception, and Diversification - Novi Puji Lestari; Muhammad Umar A; Bagastya Christian Santoso; Abdul Manap; Nirsetyo Wahdi (Goodwood, 2026)
Purpose: This study examines how investment analytics capability influences portfolio diversification effectiveness through financial technology integration and strategic risk perception in Indonesia’s emerging capital market.Research Methodology: A quantitative cross-sectional design was applied using purposive sampling of 150 investors, advisors, asset managers, and fund managers. Data were collected through a Likert-scale questionnaire and analyzed using PLS-SEM with SmartPLS 4.Results: Investment analytics capability positively influences financial technology integration (? = 0.642, p < 0.001) and strategic risk perception (? = 0.591, p < 0.001). Financial technology integration improves diversification effectiveness (? = 0.483, p < 0.001), while strategic risk perception has a negative effect (? = ?0.324, p < 0.001).Conclusion: Investment analytics capability enhances diversification through technology adoption but may also increase risk awareness that limits portfolio expansion.Limitations: This study is limited by its cross-sectional design, sample size, and focus on Indonesian investors, which may affect broader applicability.Contributions: This study contributes an integrated model linking analytical capability, fintech adoption, and risk perception, while providing insights for investors and financial institutions to improve investment strategies.